Implementation of the Contingency Leadership Style in Islamic Education at Daarul Qur'an Elementary School, Kalibata - Dela Silmi Karmila; Hasyim Asy’ari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research discusses the implementation of contingency leadership style in Islamic education at Daarul Qur'an Kalibata Elementary School. Islamic education emphasizes the development of intellectual and moral character in accordance with Islamic values. Using a descriptive qualitative method, this study collected data through observation, interviews and documentation. The results show that the contingency leadership style, which adjusts the leadership approach based on the situation and organizational needs, effectively supports the achievement of the institution's goals. Key findings include the strategic distribution of tasks by the principal, the development of interpersonal relationships, as well as the integration of innovative programs, such as experiential learning through field trips, which promote students' academic and moral growth. The study concludes that contingency leadership style is an effective and adaptive model for Islamic educational institutions, integrating modern leadership strategies and Islamic values to improve the overall quality of education.